Thermal response micelle and cross-linked micelle as well as preparation method and application thereof
Thermal response micelles are prepared by RAFT polymerization and borate ion crosslinking technology. As a water-based lubricant additive, it solves the problem that water lubricant is difficult to form a lubricating water film at the friction interface, and achieves efficient friction and wear performance and adaptive lubricating performance.
Patent Information
- Application Number
- CN202411884700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
As a lubricant, water is difficult to form a lubricating water film on the friction interface, resulting in poor bearing capacity and easy to cause cavitation wear, corrosion and leakage, limiting the application of water lubrication.
Thermal responsive micelles are prepared by RAFT polymerization technology and crosslinked micelles are formed by borate ion crosslinking. They are used as water-based lubricant additives to maintain good lubricating properties at different temperatures and loads using their temperature responsiveness and crosslinking structure.
It significantly improves the friction and wear performance of water-based lubricants, has adaptive lubricating performance, the friction coefficient remains unchanged, and the pressure bearing capacity reaches 70N, effectively solving the problem that water lubricants are difficult to form a lubricating water film at the friction interface.
Smart Images

Figure CN119708392A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricant additives, and in particular to a thermally responsive micelle and a cross-linked micelle, and a preparation method and application thereof. Background Art
[0002] Compared with lubricating oil, water has a lower viscosity. Although it produces a low friction coefficient and wear rate during the friction process, it is difficult to form a lubricating water film on the friction interface, resulting in the bearing capacity of water being worse than that of oil. This can cause serious cavitation wear, corrosion and leakage, greatly limiting the application of water lubrication. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a thermally responsive micelle and a cross-linked micelle and a preparation method and application thereof. The thermally responsive micelle prepared by the present invention can significantly improve the friction and wear performance of water-based lubricants as a water lubricating additive and has adaptive lubrication performance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a thermoresponsive micelle, comprising the following steps:
[0006] A thiocarbonate chain transfer agent, a first monomer, a first initiator and an organic solvent are mixed for RAFT polymerization to obtain a macromolecular chain transfer agent; the thiocarbonate chain transfer agent includes 2-cyano-2-propyl dithiobenzoate and / or 4-cyano-4-thiobenzoylvaleric acid; the first monomer includes one or more of glyceryl methacrylate, 2-hydroxyethyl methacrylate and ethylene oxide;
[0007] The macromolecular chain transfer agent is mixed with a second monomer, a second initiator and water to perform polymerization-induced self-assembly to obtain the thermally responsive micelle; the second monomer includes N-isopropylacrylamide.
[0008] Preferably, the first initiator and the second initiator independently include one or more of 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride and 2,2'-azobis(2-methylpropionamidine) dihydrochloride.
[0009] Preferably, the molar ratio of the thiocarbonate chain transfer agent, the first monomer and the first initiator is 1:(20-40):0.2.
[0010] Preferably, the RAFT polymerization temperature is 50-70° C. and the time is 10-15 h.
[0011] Preferably, the molar ratio of the macromolecular chain transfer agent, the second monomer and the second initiator is 1:(50-110):1.1.
[0012] Preferably, the polymerization-induced self-assembly is carried out at a temperature of 60 to 80° C. and for a time of 15 to 24 hours.
[0013] The present invention provides thermal responsive micelles prepared by the preparation method described in the above technical scheme.
[0014] The present invention provides a cross-linked micelle, which is obtained by cross-linking the thermal response micelle described in the above technical solution with borate ions.
[0015] Preferably, the molar ratio of the hydroxyl group in the thermal responsive micelle to the boron ion in the borate ion is 1:(0.052-0.2); the cross-linking temperature is 60-80° C., and the cross-linking time is 8-10 h.
[0016] The present invention provides the use of the thermally responsive micelles described in the above technical solution or the cross-linked micelles described in the above technical solution as water-based lubricant additives.
[0017] The present invention provides a method for preparing a thermoresponsive micelle, comprising the following steps: mixing a thiocarbonate chain transfer agent, a first monomer, a first initiator and an organic solvent for RAFT polymerization to obtain a macromolecular chain transfer agent; the first monomer comprises one or more of methacrylate glycerol, 2-hydroxyethyl methacrylate and ethylene oxide; the macromolecular chain transfer agent is mixed with a second monomer, a second initiator and water for polymerization-induced self-assembly to obtain the thermoresponsive micelle; the second monomer comprises N-isopropylacrylamide. The present invention connects a hydrophilic block (i.e., the first monomer) to a thiocarbonate chain transfer agent through RAFT polymerization, and then connects a hydrophobic block N-isopropylacrylamide to form a diblock copolymer and self-assemble, that is, synthesizing micelle particles with uniform structure in an aqueous solution through polymerization-induced self-assembly technology (PISA). Due to the introduction of N-isopropylacrylamide, the polymer micelle particles are temperature-responsive, and reversible transformation between spherical micelles and smaller micelles can be achieved above / below the LCST temperature (≈31°C). Specifically, above the LCST temperature, the hydrophobic effect of the N-isopropylacrylamide block drives the synthesized polymer to self-assemble in the solution to form spherical micelles. Below the LCST temperature, the N-isopropylacrylamide block dissolves in water, the hydrophobic effect (driving effect) disappears, the spherical micelles disassemble, and the polymer chains aggregate in the solution to form smaller micelles. This process is reversible multiple times.
[0018] The present invention provides a cross-linked micelle, which is obtained by cross-linking the thermoresponsive micelle described in the above technical solution with borate ions. The present invention uses borate ion cross-linking to allow the polymer, whose self-assembly structure is destroyed at a temperature below LCST, to maintain a spherical morphology at room temperature.
[0019] The present invention provides the use of the thermoresponsive micelles described in the above technical solution or the cross-linked micelles described in the above technical solution as a water-based lubricant additive. The thermoresponsive micelles or the cross-linked micelles are used as water lubricant additives for friction lubrication, and the friction and wear can be reduced at temperatures above / below LCST and under different loads, and the friction coefficient remains unchanged, which is adaptive. The results of the embodiment show that the thermoresponsive micelles or cross-linked micelles provided by the present invention are used as water-based lubricant additives, and the friction coefficient is ≤0.2, and the pressure bearing capacity can reach 70N. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The reactions involved in preparing thermoresponsive micelles for the examples;
[0021] Figure 2 Schematic diagram of the principle of cross-linked micelles in an embodiment of the present invention;
[0022] Figure 3 is the spherical micelle G in Example 1 32 -N 100 TEM images of
[0023] Figure 4 is the cross-linked micelle G in Example 3 32 -N 100 -TEM image of B;
[0024] Figure 5 The macromolecular chain transfer agent PGMA in Example 1 32 -CTA and polymer micelle G 32 -N 100 GPC test results;
[0025] Figure 6 Micelle G synthesized in Example 1 32 -N 100 Dynamic light scattering test results, Figure 6 (a) shows the change of micelle size at different temperatures, and (b) shows the change of micelle size with temperature at alternating temperatures of 25°C and 36°C.
[0026] Figure 7 Micelle G 32 -N 100 Changes in transmittance with temperature;
[0027] Figure 8 Micelle G 32-N 100 -B Changes in transmittance with temperature;
[0028] Fig. 9 Micelle G 32 -N 100 appearance that changes with temperature;
[0029] Fig.10 H2O, uncrosslinked spherical micelles G 32 -N 100 and cross-linked spherical micelles G 32 -N 100 -B The friction coefficient at 25°C varies with load;
[0030] Fig.11 H2O, uncrosslinked spherical micelles G 32 -N 100 and cross-linked spherical micelles G 32 -N 100 -B The friction coefficient changes with load at 36°C;
[0031] Fig.12 G 32 -N 100 The wear volume of the steel support surface under different load test conditions at 25℃ and 36℃ by using micelles as lubricating additives. Fig.12 (a) shows the wear volume of the steel support surface under different load test conditions at 25°C, and (b) shows the wear volume of the steel support surface under different load test conditions at 36°C.
[0032] Fig.13 G 32 -N 100 -B micelles as lubricating additives wear volume of steel support surface under different load test conditions at 25℃ and 36℃, Fig.13 (a) shows the wear volume of the steel support surface under different load test conditions at 25°C, and (b) shows the wear volume of the steel support surface under different load test conditions at 36°C. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a thermoresponsive micelle, comprising the following steps:
[0034] A thiocarbonate chain transfer agent, a first monomer, a first initiator and an organic solvent are mixed for RAFT polymerization to obtain a macromolecular chain transfer agent; the thiocarbonate chain transfer agent includes one or more of 2-cyano-2-propyl dithiobenzoate and / or 4-cyano-4-thiobenzoylvaleric acid; the first monomer includes one or more of glyceryl methacrylate, 2-hydroxyethyl methacrylate and ethylene oxide;
[0035] The macromolecular chain transfer agent is mixed with a second monomer, a second initiator and water to perform polymerization-induced self-assembly to obtain the thermally responsive micelle; the second monomer includes N-isopropylacrylamide.
[0036] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.
[0037] The invention mixes a thiocarbonate chain transfer agent, a first monomer, a first initiator and an organic solvent to carry out RAFT polymerization to obtain a macromolecular chain transfer agent.
[0038] In the present invention, the thiocarbonate chain transfer agent includes 2-cyano-2-propyl dithiobenzoate and / or 4-cyano-4-thiobenzoylvaleric acid, preferably 2-cyano-2-propyl dithiobenzoate (CPDB). In the present invention, the first monomer includes one or more of glyceryl methacrylate (GMA), 2-hydroxyethyl methacrylate and ethylene oxide (PEO), preferably glyceryl methacrylate (GMA); the first monomer is a hydrophilic monomer. In the present invention, the first initiator preferably includes one or more of 4,4'-azobis(4-cyanovaleric acid) (ACVA), 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride and 2,2'-azobis(2-methylpropionamidine) dihydrochloride, more preferably 4,4'-azobis(4-cyanovaleric acid) (ACVA); the first initiator is a thermal initiator. In the present invention, the molar ratio of the thiocarbonate chain transfer agent, the first monomer and the first initiator is preferably 1:(20-40):0.2, and can be 1:20:0.2, 1:25:0.2, 1:30:0.2, 1:32:0.2, 1:35:0.2 or 1:40:0.2. In the present invention, the organic solvent is preferably an alcohol solvent, and the alcohol solvent is preferably anhydrous ethanol. In the present invention, the solid content of the mixed solution obtained by mixing the thiocarbonate chain transfer agent, the first monomer, the first initiator and the organic solvent is preferably 40wt%.
[0039] In the present invention, the temperature of the RAFT polymerization (i.e., reversible addition-fragmentation chain transfer polymerization) is preferably 50-70°C, and may be 50°C, 60°C or 70°C, and the time is preferably 10-15h, and may be 10h, 11h, 12h, 13h, 14h or 15h. In the present invention, the RAFT polymerization is preferably carried out in the absence of oxygen, in an oil bath and under stirring, and the absence of oxygen is specifically carried out by purging with argon to remove oxygen.
[0040] The present invention adopts RAFT polymerization technology. As a kind of active free radical polymerization, RAFT polymerization has a wider reaction condition and monomer selection range, and can obtain a polymer with a narrow molecular weight distribution and good dispersibility.
[0041] After the RAFT polymerization is completed, the present invention preferably drops the obtained reaction solution into n-hexane to precipitate a solid, and dries the solid to obtain the macromolecular chain transfer agent. In an embodiment of the present invention, the drying temperature is preferably 40° C., the time is preferably 12 h, and the drying is preferably vacuum drying.
[0042] After obtaining the macromolecular chain transfer agent, the present invention mixes the macromolecular chain transfer agent with a second monomer, a second initiator and water to perform polymerization-induced self-assembly to obtain the thermal responsive micelle.
[0043] In the present invention, the second monomer includes N-isopropylacrylamide (NIPAM); the second monomer is used as a hydrophobic monomer. In the present invention, the second initiator preferably includes one or more of 4,4'-azobis(4-cyanovaleric acid) (ACVA), 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride and 2,2'-azobis(2-methylpropionamidine) dihydrochloride, more preferably 4,4'-azobis(4-cyanovaleric acid) (ACVA). In the present invention, the molar ratio of the macromolecular chain transfer agent, the second monomer and the second initiator is preferably 1:(50-110):1.1, and can be 1:50:1.1, 1:60:1.1, 1:70:1.1, 1:80:1.1, 1:90:1.1, 1:100:1.1 or 1:110:1.1. In the present invention, the water is preferably deionized water, and the solid content of the mixture obtained by mixing the macromolecular chain transfer agent with the second monomer, the second initiator and water is preferably 5-15wt%, more preferably 10wt%; within the solid content range, it is beneficial to maintain the morphology of the self-assembly. Because the morphology formed by polymerization-induced self-assembly is affected by the degree of polymerization of the hydrophilic block and the hydrophobic block, the present invention controls the ratio of the first monomer and the second monomer to obtain micelles with spherical morphology. The size of the micelles is different, but the performance is basically unchanged, so that the synthesized micelles have adaptability.
[0044] In the present invention, the temperature of the polymerization-induced self-assembly is preferably 60 to 80°C, and may be 60°C, 70°C or 80°C, and the time is preferably 15 to 24h, and may be 15h, 20h or 24h. In the present invention, the polymerization-induced self-assembly is preferably carried out under anaerobic, oil bath and stirring conditions, and the anaerobic condition is specifically purged with argon to remove oxygen. In the process of the polymerization-induced self-assembly, the macromolecular chain transfer agent and the second monomer are first polymerized by RAFT under the action of the second initiator to form a diblock copolymer. When the polymer chain reaches a certain degree, it will self-assemble, so it is a process of self-assembly while polymerizing in the reaction. After the polymerization-induced self-assembly, spherical micelles with a certain degree of polymerization are obtained.
[0045] Taking the first monomer as glyceryl methacrylate (GMA), the thiocarbonate chain transfer agent as 2-cyano-2-propyl dithiobenzoate (CPDB), and the second monomer as N-isopropylacrylamide (NIPAM) as an example, the reactions involved in preparing the thermal responsive micelles in the embodiment of the present invention are as follows: Figure 1 shown.
[0046] The present invention adopts polymerization induced self-assembly technology (PISA) to synthesize spherical nano micelle particles in water. Compared with traditional self-assembly technology, spherical micelle particles with uniform structure can be synthesized in situ in the same aqueous solution within a wider concentration range (5-15%), and can be polymerized and self-assembled in the solution at the same time, which is simple to operate.
[0047] The present invention provides thermal responsive micelles prepared by the preparation method described in the above technical scheme.
[0048] In the present invention, the number average molecular weight of the thermoresponsive micelle is ≥16000. In the present invention, the thermoresponsive micelle has temperature responsiveness because of the poly N-isopropylacrylamide (PNIPAM) therein, so that the micelle has thermoresponsiveness. In the present invention, the LCST temperature (i.e., lower critical solution temperature) of the thermoresponsive micelle is ≈31°C. Since the self-assembly process is a physical process, the PNIPAM block is hydrophobic above the LCST temperature, and the hydrophobic effect drives the polymer to self-assemble in the solution to form spherical micelles. When the temperature is below the LCST temperature, the PNIPAM polymer is hydrophilic, the hydrophobic effect disappears, and the self-assembled structure is destroyed. The present invention subsequently adds a cross-linking agent for cross-linking to keep the spherical morphology at room temperature.
[0049] The present invention provides a cross-linked micelle, which is obtained by cross-linking the thermal response micelle described in the above technical solution with borate ions.
[0050] In the present invention, the molar ratio of the hydroxyl group (from the first monomer segment) in the thermally responsive micelle to the boron ion in the borate ion is preferably 1: (0.052-0.2), which can be 1: 0.052, 1: 0.08, 1: 0.12, 1: 0.16 or 1: 0.2; the borate ion is preferably provided by sodium borate, and in an embodiment of the present invention, the sodium borate is specifically sodium tetraborate decahydrate (Na2B4O7·10H2O). In the present invention, the borate ion is used as a crosslinking agent. The present invention preferably adds a sodium tetraborate aqueous solution to the reaction solution containing micelles obtained by the above-mentioned polymerization-induced self-assembly to carry out a crosslinking reaction, and the concentration of the sodium tetraborate aqueous solution is preferably 0.084 mol / L. In the present invention, the temperature of the crosslinking is preferably 60-80°C, which can be 60°C, 70°C or 80°C, and the time is preferably 8-10h, which can be 8h, 9h or 10h.
[0051] Figure 2Schematic diagram of the principle of crosslinked micelles according to the embodiments of the present invention. Taking the thermoresponsive micelles synthesized with glycerol methacrylate (GMA) as the first monomer as an example, borate ions are introduced as crosslinking agents, and the micelle shell is crosslinked by forming B-O bonds with the -OH groups on polyglycerol methacrylate (PGMA), thereby stabilizing the micelles and preventing the micelles from collapsing during the inevitable cooling process (room temperature < LCST). Figure 2 In Figure 2 , the blue line represents the polyglycerol methacrylate chain segment, the red line represents the poly(N-isopropylacrylamide) (PNIPAM) chain segment, and the green line represents the B-O bond.
[0052] The crosslinked micelles provided by the present invention still have good temperature responsiveness. When the temperature rises, the PNIPAM chain segments in the crosslinked micelles are insoluble in water, and the morphology of the inner layer crosslinked by loose polymer chains becomes compact, making the size of the overall spherical micelles smaller.
[0053] The present invention provides the application of the thermoresponsive micelles or the crosslinked micelles described in the above technical solutions as water-based lubricant additives. Compared with pure water, the thermoresponsive micelles and crosslinked micelles provided by the present invention have obvious lubricating effects as water-based lubricant additives. The thermoresponsive micelles maintain a constant friction coefficient at room temperature (25°C) despite the destruction of the self-assembled structure, having self-adaptive lubrication performance, and the crosslinked micelles maintain a constant friction coefficient compared with the uncrosslinked micelles during lubrication. In the embodiments of the present invention, after the macromolecular chain transfer agent is mixed with the second monomer, the second initiator, and water for polymerization-induced self-assembly, and further crosslinked with borate ions, no post-treatment is required, and the obtained aqueous solution containing thermoresponsive micelles or crosslinked micelles is directly used as a water-based lubricant, and the thermoresponsive micelles or crosslinked micelles therein are the water-based lubricant additives.
[0054] To further illustrate the present invention, the thermoresponsive micelles and crosslinked micelles provided by the present invention, their preparation methods and applications will be described in detail below with reference to examples, but they should not be construed as limiting the protection scope of the present invention.
[0055] In each example, glycerol methacrylate (GMA) and 4,4'-azobis(4-cyanovaleric acid) (ACVA) were purchased from Anhui Zesheng Technology Co., Ltd., and 2-cyano-2-propyl dithiobenzoate (CPDB) was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0056] Example 1
[0057] The preparation of thermoresponsive micelles involves the reaction as Figure 1 shown, and the preparation steps are as follows:
[0058] (1) Preparation of polyglycerol methacrylate (PGMA) macromolecular chain transfer agent:
[0059] Chain transfer agent CPDB (1 mmol), GMA (32 mmol), ACVA (0.2 mmol) and anhydrous ethanol (10.27 mL) were added to a 50 mL Schlenk bottle at a molar ratio of [CPDB]: [GMA]: [ACVA] = 1: 32: 0.2. The mixture was mixed (solid content was 40% w / w) and purged with argon for 30 min to remove oxygen. The sealed bottle was stirred in an oil bath at 60° C. for 11 h. The reacted solution was dropped into n-hexane to precipitate solids, which were dried in a vacuum oven at 40° C. for 12 h to obtain a macromolecular chain transfer agent with a degree of polymerization of DP = 32. The sample was named PGMA 32 -CTA.
[0060] (2) Preparation of thermoresponsive micelles (PGMA with a solid content of 10% w / w was prepared in deionized water) 32 -PNIPAM 100 Diblock copolymers):
[0061] Add the macromolecular chain transfer agent PGMA into a 50 mL Schlenk flask. 32 -CTA (0.1 mmol), NIPAM (N-isopropylacrylamide, 11 mmol), ACVA (0.11 mmol) and H2O (16.3 mL), the molar ratio of [PGMA 32 -CTA]:[NIPAM]:[ACVA]=1:110:1.1, purged with argon for 30 min to remove oxygen, and then stirred in an oil bath at 70 °C for 20 h. The resulting polymer micelles were treated with PGMA 32 -PNIPAM 100 It is abbreviated as G 32 -N 100 , the degree of polymerization of NIPAM DP = 100.
[0062] Example 2
[0063] The molar ratio in Example 1 was changed to: [PGMA 32 -CTA]:[NIPAM]:[ACVA]=1:68:1.1, the rest is the same as in Example 1, the obtained polymer is treated with PGMA 32 -PNIPAM 62 It is abbreviated as G 32 -N 62 .
[0064] Example 3
[0065] Cross-linked micelles (denoted as PGMA 32 -PNIPAM 100 -B) Preparation:
[0066] G was synthesized by step (2) of Example 1 32 -N 100 After the micelles were formed, a sodium tetraborate decahydrate aqueous solution (0.084 mol / L, 1 mL) was added to the reaction solution at a molar ratio of [-OH]:[Na2B4O7·10H2O]=1:0.013 for a cross-linking reaction. The reaction was carried out at 70°C under sealed conditions for 8 h to obtain cross-linked micelles, i.e., PGMA. 32 -PNIPAM 100 -B, abbreviated as G 32 -N 100 -B.
[0067] The micelles prepared in the examples and the cross-linked micelles prepared in the examples were tested as follows:
[0068] (1) Polymer G synthesized in Example 1 32 -N 100 The samples were diluted with deionized water at 36°C and tested by transmission electron microscopy (TEM). Figure 3 As shown, it is proved that the self-assembly is spherical. 32 -N 100 -B was diluted at room temperature and the samples were prepared for TEM testing. Figure 4 As shown, a spherical morphology was observed, demonstrating successful cross-linking.
[0069] (2) The macromolecular chain transfer agent PGMA in Example 1 32 -CTA and polymer micelle G 32 -N 100 GPC (gel permeation chromatography) test, the results are as follows Figure 5 As shown, it proves that the molecular weight distribution of the polymer is uniform.
[0070] (3) Micelle G synthesized in Example 1 32 -N 100 Dynamic light scattering (DLS) test was performed, and the results were as follows Figure 6 As shown, Figure 6 (a) shows the change of micelle size at different temperatures, and (b) shows the change of micelle size with temperature at alternating temperatures of 25°C and 36°C.
[0071] The solution was diluted and the size of the synthesized spherical micelles was measured by dynamic light scattering test. Figure 6 In (a), we can see that the size of the particles in the solution is small at low temperature. When the temperature is greater than the LCST, the diameter of the particles in the solution suddenly increases and then remains unchanged, proving that the synthesized micelles are temperature responsive. The change in the particle size of the micelles with temperature was measured alternately at two temperatures (36°C and 25°C), as shown in Figure 2. Figure 6 As shown in (b), the particle size can change repeatedly with temperature, proving that the synthesized spherical micelles are temperature reversible.
[0072] (4) Measurement of micelle G by UV spectrophotometer 32 -N 100 The change of transmittance with temperature is measured at different wavelengths of 200-800nm and in the temperature range of 25-45℃. The test results are as follows: Figure 7 As shown. Figure 7 It can be seen that below the LCST temperature, the transparency of the solution is high, and when the temperature is greater than the LCST temperature, the transmittance of the solution suddenly decreases, proving that the synthesized polymer is temperature responsive.
[0073] The micelle G was measured by UV spectrophotometry under the same conditions. 32 -N 100 -B The change of transmittance with temperature, the test results are as follows Figure 8 As shown. Figure 8 It can be seen that the cross-linked spherical micelles still have good temperature responsiveness. (Note: Figure 7 and Figure 8 The focus is on the change in transmittance above and below the LCST temperature, mainly distinguishing the changes in the blue line and the red line. Figure 7 For example, when the temperature is above 32°C, micelles are formed, the solution becomes insoluble, and the solution as a whole is opaque. Therefore, the temperature curves above 32°C overlap, while the solution is a transparent solution below the LCST, and the curves overlap.
[0074] (5) Polymer micelle G 32 -N 100 Appearance changes with temperature
[0075] Fig. 9 is the polymer micelle G 32 -N 100 The appearance changes with temperature. Due to its temperature responsiveness, when the temperature is higher than LCST, the polymer self-assembles into micelles and the solution changes from transparent to opaque. Polymer micelle G 32 -N 62 Appearance changes with temperature Fig. 9 Be consistent.
[0076] (6) The tribological behavior of micelles was studied using a friction and wear tester in a ball-on-disk reciprocating motion mode. The friction test was carried out at two characteristic temperatures, 25°C and 36°C, which correspond to the thermal expansion of the micelles. The test frequency was 25 Hz, the amplitude was 1 mm, the loads were 20 N, 50 N and 70 N respectively, the friction pair was a steel support and a steel ball, and each test lasted 20 minutes. To ensure the reliability of the results, each sample was tested three times under each condition, and the average value obtained was statistically significant.
[0077] Fig.10 and Fig.11 H2O, uncrosslinked spherical micelle G 32 -N 100 and cross-linked spherical micelles G 32 -N 100 -B friction coefficient at 25℃ and 36℃ varies with load. Friction test proves that spherical micelle G 32 -N 100 It is a water lubricating additive. Compared with pure water, its friction coefficient is significantly lower, and its friction coefficient remains unchanged with changes in temperature and load, and has adaptive lubricity. 32 -N 100 -B lubricates compared to uncrosslinked micelles G 32 -N 100 The friction coefficient remained unchanged (≤0.2), proving that the polymer self-assembly process did not affect the friction coefficient.
[0078] Fig.12 G 32 -N 100 The wear volume of the steel support surface under different load test conditions at 25℃ and 36℃ by using micelles as lubricating additives. Fig.12 (a) shows the wear volume of the steel support surface under different load test conditions at 25°C, and (b) shows the wear volume of the steel support surface under different load test conditions at 36°C. The corresponding data are listed in Table 1. Fig.12 As shown in Table 1, compared with pure water lubrication, G 32 -N 100 When micelles are used as lubricating additives, the wear volume is significantly reduced at loads of 20 to 70 N. Fig.10 The friction coefficient is also significantly reduced, indicating that it has good lubrication performance and adaptive lubricity.
[0079] Fig.13 G 32 -N 100 -B micelles as lubricating additives wear volume of steel support surface under different load test conditions at 25℃ and 36℃, Fig.13(a) shows the wear volume of the steel support surface under different load test conditions at 25°C, and (b) shows the wear volume of the steel support surface under different load test conditions at 36°C. The corresponding data are listed in Table 1. Fig.13 As can be seen from the results in Table 1, compared with the uncrosslinked micelles, G 32 -N 100 -B micelles as lubricating additives have a basically unchanged wear volume, indicating that during the lubrication process, as the temperature increases, the self-assembly process of the polymer does not affect its lubricating performance.
[0080] Table 1G 32 -N 100 and G 32 -N 100 -B micelles as lubricating additives wear volume of steel support surface under different load test conditions at 25℃ and 36℃
[0081]
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a thermally responsive micelle, characterized in that: The following steps are involved: A thiocarbonate chain transfer agent, a first monomer, a first initiator and an organic solvent are mixed for RAFT polymerization to obtain a macromolecular chain transfer agent; the thiocarbonate chain transfer agent includes 2-cyano-2-propyl dithiobenzoate and / or 4-cyano-4-thiobenzoylvaleric acid; the first monomer includes one or more of glyceryl methacrylate, 2-hydroxyethyl methacrylate and ethylene oxide; The macromolecular chain transfer agent is mixed with a second monomer, a second initiator and water to perform polymerization-induced self-assembly to obtain the thermally responsive micelle; the second monomer includes N-isopropylacrylamide.
2. The preparation method according to claim 1, characterized in that: The first initiator and the second initiator independently include one or more of 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride and 2,2'-azobis(2-methylpropionamidine) dihydrochloride.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the thiocarbonate chain transfer agent, the first monomer and the first initiator is 1:(20-40):0.
2.
4. The preparation method according to claim 1, characterized in that: The RAFT polymerization is carried out at a temperature of 50 to 70° C. and for a time of 10 to 15 hours.
5. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the macromolecular chain transfer agent, the second monomer and the second initiator is 1:(50-110):1.
1.
6. The preparation method according to claim 1, characterized in that: The polymerization-induced self-assembly is carried out at a temperature of 60 to 80° C. and for a time of 15 to 24 hours.
7. The thermally responsive micelles prepared by the preparation method according to any one of claims 1 to 6.
8. A cross-linked micelle, characterized in that The thermoresponsive micelles according to claim 7 are cross-linked with borate ions.
9. The cross-linked micelle according to claim 8, characterized in that The molar ratio of the hydroxyl group in the thermal response micelle to the boron ion in the borate ion is 1:(0.052-0.2); the cross-linking temperature is 60-80°C and the time is 8-10h.
10. Use of the thermoresponsive micelle according to claim 7 or the cross-linked micelle according to claim 8 or 9 as a water-based lubricant additive.
Citation Information
Patent Citations
Polymer molecule brush supported catalyst as well as synthesis method and application of catalyst
CN104338555A
Hydrogel condom and preparation method thereof
CN106543356A
Stretchable self-repairing hydrogel based on dynamic covalent crosslinking agent and preparation method thereof
CN108752370A
Nano lubricating additive for regulating and controlling interface friction as well as preparation method and application of nano lubricating additive
CN113337327A
Polymerization-induced self-assembly spherical micelle particles as well as preparation method and application thereof
CN116693778A